2008
DOI: 10.1097/qai.0b013e3181685727
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV Infection and HIV/HCV Coinfection With C-Reactive Protein Levels

Abstract: In the absence of HCV coinfection, HIV infection is associated with higher CRP levels in men. HCV coinfection is associated with lower CRP levels in men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(49 citation statements)
references
References 41 publications
6
42
1
Order By: Relevance
“…In our cohort of women, median CRP levels were 46–74% and 24% lower than those reported in other cohort studies of HIV-infected women [10], [31] and HIV/HCV-infected women [10], respectively. Our study was conducted in the era of potent antiretroviral therapy, which is reflected in high median CD4 counts (>500 cells/ml) and could explain the lower IL-6 and CRP levels than reported in other studies.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In our cohort of women, median CRP levels were 46–74% and 24% lower than those reported in other cohort studies of HIV-infected women [10], [31] and HIV/HCV-infected women [10], respectively. Our study was conducted in the era of potent antiretroviral therapy, which is reflected in high median CD4 counts (>500 cells/ml) and could explain the lower IL-6 and CRP levels than reported in other studies.…”
Section: Discussioncontrasting
confidence: 77%
“…Among the HIV-monoinfected women, current smoking and marijuana use were associated with higher CRP levels, as was a higher CD4 count. Smoking has been associated with higher CRP levels [10]; whether or not there is a direct association of marijuana with higher CRP levels is unclear. Although unexpected, the association of higher CD4 could represent a restoration to health, and thus restoration of fat stores and higher CRP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from HIV studies also support a hypothesized HIV-mediated reduction in hepatocyte synthetic function. Levels of C-reactive protein (CRP), an acute phase reactant released by hepatocytes, were modestly higher among HIV mono-infected individuals and actually lower among those with HIV/HCV co-infection, when compared to uninfected controls [66]. In addition, while IL-6 and D-dimer levels decline with initiation of ART, CRP levels fail to improve or actually increase in some studies [67, 68].…”
Section: Altered Composition Of Coagulation Factorsmentioning
confidence: 99%
“…11214045 In the Strategic Management of Anti-Retroviral Therapy Study (SMART), it has been shown that hsCRP and IL-6 levels are associated with HIV viral replication and CVD and all-cause mortality risk. 81446 In SMART, higher levels of hsCRP and IL-6 at baseline were strongly associated with increased risk for mortality both over the short- and long-term (CVD and non-CVD related).…”
Section: Markers Of Inflammationmentioning
confidence: 99%